Lichen planopilaris with classic dermoscopic features associated with findings reminiscent of alopecia areata. - Patankar, S.S.; Phiske, M.; Joshi, R.; Someshwar, S. (European Journal of Pediatric Dermatology, 2025)
Lichen planopilaris (LPP) is a rare variant of lichen planus potentially leading to cicatricial alopecia on the scalp. Alopecia areata (AA) is an autoimmune disorder that causes reversible non-cicatricial alopecia. We describe the case of a 15-year-old girl with tubercular lymphadenitis, depression, and hypothyroidism, presenting with multiple, well-defined, erythematous, and hyperpigmented alopecic patches in the frontal parietal region and on the vertex for 1 month. Dermoscopy showed classic findings of lichen planopilaris associated with features of alopecia areata, suggesting a colocalization of the two diseases, as previously described, albeit rarely, in the literature.